DESIGN AND IMPLEMENTATION OF AN UNDERGRADUATE COURSE ON SUBTITLING - Villanueva Jordán, Iván Alejandro (2016)
This paper presents the curricular profile of an introductory course to subtitling in a university translation program in Lima, Peru. To this aim, the design elements that lead to its implementation are documented:  contents per unit, methodology and evaluation. The paper is expected to evidence the key points of the proposal and to promote the practical application of audiovisual translation pedagogy.